2019
DOI: 10.3390/app9183721
|View full text |Cite
|
Sign up to set email alerts
|

Insight into Pretreatment Methods of Lignocellulosic Biomass to Increase Biogas Yield: Current State, Challenges, and Opportunities

Abstract: Lignocellulosic biomass is recalcitrant due to its heterogeneous structure, which is one of the major limitations for its use as a feedstock for methane production. Although different pretreatment methods are being used, intermediaries formed are known to show adverse effect on microorganisms involved in methane formation. This review, apart from highlighting the efficiency and limitations of the different pretreatment methods from engineering, chemical, and biochemical point of views, will discuss the strateg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
74
0
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 193 publications
(79 citation statements)
references
References 193 publications
(216 reference statements)
1
74
0
4
Order By: Relevance
“…In contrast, a decrease in methane yield was reported by Li et al [54] where a 13.8% drop in methane yield resulted from microwave treatment of Pennisetum hybrid grass at 1180 W, frequency 2450 MHz, and temperature up to 260 • C. MWP can generate inhibitory by-products such as HMF and furfural and cause losses of volatile and biodegradable matter due to exposure to the high microwave irradiation without temperature control especially in intense heating rate represented by high wattage and lack of sufficient liquid to distribute the heat [55,56]. These factors, solid to liquid ratio, exposure time, and microwave power, all constitute energy intensity.…”
Section: Difference In Biodegradability Of the Pretreated Grass Biomassmentioning
confidence: 99%
“…In contrast, a decrease in methane yield was reported by Li et al [54] where a 13.8% drop in methane yield resulted from microwave treatment of Pennisetum hybrid grass at 1180 W, frequency 2450 MHz, and temperature up to 260 • C. MWP can generate inhibitory by-products such as HMF and furfural and cause losses of volatile and biodegradable matter due to exposure to the high microwave irradiation without temperature control especially in intense heating rate represented by high wattage and lack of sufficient liquid to distribute the heat [55,56]. These factors, solid to liquid ratio, exposure time, and microwave power, all constitute energy intensity.…”
Section: Difference In Biodegradability Of the Pretreated Grass Biomassmentioning
confidence: 99%
“…General chemical composition (as % of dry weight), and composition (%) of CHCl3-EtOH extractable compounds of olive stones (adapted from [27,29]). In addition to its main use being as biomass and fuel, olive stones are useful thanks to their physical properties and useful chemical components [30]. The three main components of lignocellulosic olives are interesting enough to be separated by fractionation.…”
Section: Olive Stones' Chemical Compositionmentioning
confidence: 99%
“…Physical, thermal, mechanical properties, tensile modulus [29] differential scanning calorimetry (DSC), thermogravimetric analysis (TGA) [27] Filler [30] Polyvinyl chloride (PVC) TGA In plastic-based materials [31] Polypropylene (PP)…”
Section: Thermoplastic Polymermentioning
confidence: 99%
See 1 more Smart Citation
“…Other studies have reported that pretreatment of lignocellulosic biomass (LB) aids to overcome recalcitrance through the combination of chemical and structural changes to the lignin and carbohydrates. Some of the different methods of pretreatment include physical; namely, mechanical pretreatment, physicochemical; namely, steam explosion, chemical; namely, alkali and acidic pretreatment, and biological; namely, manure addition or mixed microorganisms [6,7]. Nonetheless, these traditional methods of pretreatment are cost-intensive, as additional chemicals or energy are required [8].…”
Section: Introductionmentioning
confidence: 99%